ASSESSING THE IMPACT OF ENVIRONMENTAL HAZARDS ON EDUCATIONAL FACILITY STRUCTURES IN KARANGASEM REGENCY: IMPLICATIONS FOR RISK MITIGATION - I Putu Ellsa Sarassantika; Gde Bagus Andhika Wicaksana; Kadek Tania Utami Putri (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
Educational facilities in Karangasem Regency face significant risks from environmental factors such as seismic activity, unstable soils, and extreme weather, which contribute to structural damage. This study aims to assess the extent of building damage in these facilities and understand its relationship with surrounding environmental conditions to inform risk mitigation strategies. A comprehensive method was employed, combining field surveys, structural inspections, and Geographic Information System (GIS) mapping. Damage levels were classified into minor, moderate, severe, and total destruction, based on structural and non-structural indicators. Disaster risk, including potential strong winds, potential floods, potential landslides, potential droughts, and potential earthquakes, were integrated to identify patterns and correlations with building damage. The findings revealed that 16.7% and 7.7% of facilities experienced light damage and moderate damage respectively, predominantly in areas with high winds, landslides, and earthquakes potential. Additionally, topographical challenges, such as slope instability, were identified as major contributors to damage severity. GIS analysis highlighted clusters of high-risk zones, underscoring the spatial relationship between environmental conditions and damage distribution. The study concludes that the integration of structural assessments with environmental analysis provides a robust framework for evaluating building vulnerabilities. Recommendations include the adoption of disaster-resistant construction materials, enhanced maintenance protocols, and strategic land-use planning. These measures are essential for mitigating risks and ensuring the safety and sustainability of educational facilities in Karangasem Regency. This research offers valuable insights into disaster risk management and contributes to developing resilient infrastructure in hazard-prone regions.